2017
DOI: 10.1371/journal.ppat.1006748
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory monocytes mediate control of acute alphavirus infection in mice

Abstract: Chikungunya virus (CHIKV) and Ross River virus (RRV) are mosquito-transmitted alphaviruses that cause debilitating acute and chronic musculoskeletal disease. Monocytes are implicated in the pathogenesis of these infections; however, their specific roles are not well defined. To investigate the role of inflammatory Ly6ChiCCR2+ monocytes in alphavirus pathogenesis, we used CCR2-DTR transgenic mice, enabling depletion of these cells by administration of diptheria toxin (DT). DT-treated CCR2-DTR mice displayed mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 79 publications
2
68
0
Order By: Relevance
“…This result is consistently observed on the UMAP biplot, which showed that mock‐infected joints were lacking an infiltrating leukocyte population corresponding to PhenoGraph clusters 1, 13, 14, 19, 29, 30, 32, 33 (Fig C–E). These clusters are collectively made up of populations expressing CD11b + , CD64 + , Ly6C hi , and MHC‐II + (Figs E and EV3B), indicative of inflammatory monocytes (Haist et al , ). Interestingly, the RH‐CHIKV‐infected group diverged the most from WT‐CHIKV and showed the highest level of similarity to the mock‐infected group (Fig B).…”
Section: Resultsmentioning
confidence: 99%
“…This result is consistently observed on the UMAP biplot, which showed that mock‐infected joints were lacking an infiltrating leukocyte population corresponding to PhenoGraph clusters 1, 13, 14, 19, 29, 30, 32, 33 (Fig C–E). These clusters are collectively made up of populations expressing CD11b + , CD64 + , Ly6C hi , and MHC‐II + (Figs E and EV3B), indicative of inflammatory monocytes (Haist et al , ). Interestingly, the RH‐CHIKV‐infected group diverged the most from WT‐CHIKV and showed the highest level of similarity to the mock‐infected group (Fig B).…”
Section: Resultsmentioning
confidence: 99%
“…Macrophage activation has a crucial role in articular and muscular inflammation-derived lesions in RRV and CHIKV infection (22,44). In addition, the production of type I IFN by activated inflammatory monocytes has been suggested as crucial to control acute RRV infection in mice (25). Here, we observed moderate cellular infiltrate on the focus of necrosis and high expression of inflammatory mediators in the muscle of MAYV infected mice, including TNF levels that may contribute to tissue damage.…”
Section: Discussionmentioning
confidence: 52%
“…Similar diversity and intensity of clinic signals were observed in WT 11-dayold mice ( Table 1). We also investigated MAYV infection in adult recombination activation gene-1 deficient mice (RAG1 -/-), which do not maturate B and T lymphocytes (26), used as a model to investigate the involvement of adaptive immunity in diseases (25). MAYV infection of adult RAG1 -/mice did not cause lethality, weight loss, and even other clinical signals observed in young WT and adult IFNAR -/mice (Table 1).…”
Section: Mayv Inoculation Induces Clinical Signs Of Infection In Younmentioning
confidence: 99%
See 1 more Smart Citation
“…Total RNA from Vero cells infected with dengue virus type 2 (New Guinea C), influenza A (H3N2 Udorn) or mock-infected was extracted using Trizol (Thermo-Scientific) [19] and provided by Alex Stabell and Sara Sawyer (University of Colorado, Boulder). Total RNA extracted from whole quad muscle collected 5 days post-infection from C57BL/6J mice that were mock-infected or infected with Ross River virus (T48) as described in [20] was provided by Kelsey Haist and Thomas Morrison (University of Colorado, Anschutz Medical Campus). All mouse studies were performed at the University of Colorado Anschutz Medical Campus (Animal Welfare Assurance #A 3269-01) using protocols approved by the University of Colorado Institutional Animal Care and Use Committee and in accordance with the recommendations in the Guide for the Care and Use of Laboratory Animals of the National Institutes of Health.…”
Section: Dsrna Purificationmentioning
confidence: 99%